2012
DOI: 10.1007/s00035-012-0100-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating herbaceous plant biomass in mountain grasslands: a comparative study using three different methods

Abstract: It is a challenge to find effective methods to estimate biomass over a large range of biomass values in diverse plant communities, such as typically found in mountain grasslands. We compared the performance of three non-destructive methods for estimating plant biomass (3D quadrat: a point quadrat method, plate meter: a measure of physical volume, and visual estimation: a component of the BOTANAL method) in mountain grasslands. We tested whether: (1) all methods performed equally in terms of linearity of estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
(32 reference statements)
1
25
0
Order By: Relevance
“…Our results are in agreement with the findings of Döbert et al (2015), who found that even a semi-quantitative assessment based on Braun-Blanquet scale can provide a reliable proxy for aboveground biomass. Similar to our results, Redjadj et al (2012) also found that visual cover estimation can be accurate in estimating biomass, although they estimated biomass directly (and not cover), and estimation procedure was preceded by a training series. The relatively weak performance of point intercept method found in our study is in contrast to comparative studies that found good accuracy for this method (Byrne et al 2011, Godínez-Alvarez et al 2009).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results are in agreement with the findings of Döbert et al (2015), who found that even a semi-quantitative assessment based on Braun-Blanquet scale can provide a reliable proxy for aboveground biomass. Similar to our results, Redjadj et al (2012) also found that visual cover estimation can be accurate in estimating biomass, although they estimated biomass directly (and not cover), and estimation procedure was preceded by a training series. The relatively weak performance of point intercept method found in our study is in contrast to comparative studies that found good accuracy for this method (Byrne et al 2011, Godínez-Alvarez et al 2009).…”
Section: Discussionsupporting
confidence: 88%
“…For all datasets, the relationships between biomass proxies as explanatory variables (visually estimated cover, number of point hits, or NDVI) and harvested biomass as dependent variable were tested by linear regression (Faraway, 2005), in accordance with numerous relevant studies (Jonasson, 1988, Redjadj et al 2012, Röttgermann et al 2000. The accuracy of the studied proxies was characterized by the coefficient of determination (R 2 ).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between biomass proxies and harvested biomass were tested by linear regression models for each year separately (Faraway, 2005) in accordance with numerous similar methodological studies (Redjadj et al, 2012;Röttgermann et al, 2000). Goodness of the fitted calibration lines was measures by coefficient of determination (R 2 ) and root mean squared error (RMSE).…”
Section: Discussionmentioning
confidence: 99%
“…At this time, leaf damage is not only most relevant from the point of view of agriculture, but also from the ones of ecology and conservation, simply because subsequent mowing and grazing remove large parts of the host plants and pathogens. In addition to taking vegetation records, in each plot we harvested biomass 4 cm above ground in a randomly selected area of 0.5 m 9 0.5 m to assess standing crop (Redjadj et al 2012). At the same time, in the 215 parcels we collected one leaf of each of ten plants of the three functional plant groups graminoids (Poaceae, Carex, and Luzula), legumes, and non-legume forbs (except for thistles and orchids).…”
Section: Leaf Samplingmentioning
confidence: 99%